2016
DOI: 10.1111/petr.12747
|View full text |Cite
|
Sign up to set email alerts
|

Can Destination Therapy be implemented in children with heart failure? A study of provider perceptions

Abstract: DT is an established final therapeutic choice in adult patients with severe heart failure who do not meet criteria for cardiac transplantation. Patients are given VADs, without the prospect of care escalation to transplantation. VADs are now established therapy for children and are currently used as a bridge until transplantation can be performed or heart failure improves. For children who present in severe heart failure but do not meet transplantation criteria, the question has emerged whether DT can be offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…In pediatrics the concept of destination therapy may be different when compared to adult provider beliefs. Char et al suggested that 'providers are reaching a point where they can consider long-term VAD for patients with contraindications to transplant that have the potential to improve, or even can be stabilized long enough for future therapies to emerge [34]. In this sense, destination therapy in children may become more like a long bridge to decision, rather than the adult concept of destination therapy as a true 'destination' [34].…”
Section: Emerging Conceptsmentioning
confidence: 99%
“…In pediatrics the concept of destination therapy may be different when compared to adult provider beliefs. Char et al suggested that 'providers are reaching a point where they can consider long-term VAD for patients with contraindications to transplant that have the potential to improve, or even can be stabilized long enough for future therapies to emerge [34]. In this sense, destination therapy in children may become more like a long bridge to decision, rather than the adult concept of destination therapy as a true 'destination' [34].…”
Section: Emerging Conceptsmentioning
confidence: 99%
“…In the current issue of the journal, Char et al have begun to explore this topic from the perspective of providers through semi‐structured interview at one of the few pediatric VAD programs that has implanted VADs as destination therapy (DT) as declared at the time of implantation. The study is limited by the single‐center nature of the study; however, the comments documented in the study seem to accurately reflect the opinion of many providers within the pediatric VAD community and thus are novel and important data in what is likely to be a growing patient population.…”
mentioning
confidence: 99%
“…In children, VADs have also begun to assume an important role in the treatment of end-stage heart failure (O'Connor and Rossano 2014), and pediatric VAD DT has also begun to emerge as a clinical possibility for children with end-stage heart failure who are ineligible for transplantation (Char et al 2016). Although there are accepted criteria for VAD support in adults, indications and contraindications for VAD support in children are still being established (Feldman et al 2013;Miller and Guglin 2013).…”
mentioning
confidence: 99%
“…Discontinuing VAD in a child can be emotionally very difficult for providers as well as families, much more so than VAD discontinuation in the adult DT population (Char et al 2016). Similarly, with improving VAD technologies that could allow safe, long-term VAD use until suitable transplantation, and with continuing improvements in outcomes for diseases that contraindicate transplant, like muscular dystrophies, clinicians have not yet been ready to accept "destination" for all of their patients, instead viewing pediatric VAD as a bridge and longer bridge (Char et al 2016). Barg and colleagues (2017) describe patients as entering a liminal, or undefined, state of being neither sick nor healthy, with no culturally scripted role or identity once they undertake VAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation